The economic context, embeddedness and immigrant entrepreneurs - Razin, Eran; Kloosterman, Robert; Rath, Jan, 1956- (International journal of entrepreneurial behavior & research, 2002)
The last few decades have shown a remarkable reappraisal of the smallbusiness sector. Since the 1970s, the gloomy orthodoxy notwithstanding, alarge number of people have set up shop and managed to survive in anincreasingly global economy. Their role in the economy has been publiclyacknowledged by now, as has been amply demonstrated by the drasticliberalization of their regulatory environment.